2017
DOI: 10.1186/s12920-017-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus strategy in genes prioritization and combined bioinformatics analysis for preeclampsia pathogenesis

Abstract: BackgroundPreeclampsia is a multifactorial disease with unknown pathogenesis. Even when recent studies explored this disease using several bioinformatics tools, the main objective was not directed to pathogenesis. Additionally, consensus prioritization was proved to be highly efficient in the recognition of genes-disease association. However, not information is available about the consensus ability to early recognize genes directly involved in pathogenesis. Therefore our aim in this study is to apply several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 88 publications
1
30
0
Order By: Relevance
“…To increase the sample sizes, several meta-analyses on reported microarray datasets were published since 2012. [58][59][60][61][62][63] In 2015, Kaartokallio et al reported the first RNA-seq study on PE. 46 To obtain a consensus PE-associated genes, we collected 1,177 genes from literature, including 6 meta-analysis papers, 58-63 1 literaturecuration paper 64 and 1 RNA-seq research paper.…”
Section: The Degs Overlapped With Pe-associated Genes From the Literamentioning
confidence: 99%
“…To increase the sample sizes, several meta-analyses on reported microarray datasets were published since 2012. [58][59][60][61][62][63] In 2015, Kaartokallio et al reported the first RNA-seq study on PE. 46 To obtain a consensus PE-associated genes, we collected 1,177 genes from literature, including 6 meta-analysis papers, 58-63 1 literaturecuration paper 64 and 1 RNA-seq research paper.…”
Section: The Degs Overlapped With Pe-associated Genes From the Literamentioning
confidence: 99%
“…Second, Gene Ontology enrichment analysis and functional ingenuity pathway analysis have been used to identify potential signaling pathways, suggesting that various physiological processes, such as chronic inflammation characterized by local or systemic oxidative stress (12,16) and innate and adaptive immune system (13,14), angiogenesis, hypoxia, apoptosis and placental development are implicated in the pathophysiology of preeclampsia (15). The following biological processes are also enriched in preeclampsia: Metabolism, cell cycle regulation, implantation, decidualization, cell-cell adhesion, the response to cAMP, the transforming growth factor (TGF)-β signaling pathway, Wnt signaling pathway and the Hippo signaling pathway (35,(42)(43)(44)(45). The abnormal spiral artery remodeling leads to a state of relative ischemia and to an increase in oxidative stress.…”
Section: Gene Expression Profiling and Functional Pathway Analysis Ofmentioning
confidence: 99%
“…The effects of adiponectin on the cardiovascular system in hypertensive patients are believed to be partially mediated by activation of 5' active adenosine monophosphate protein kinase and pathway cyclooxygenase-2, reduces endothelial cell apoptosis, promotes the production of nitric oxide, decreased activity in tumor necrosis factoralpha (TNF-α), and prevented atherosclerotic proliferation and smooth muscle cell migration [49]. In addition, there is a consensus strategy to improve early detection and enrichment of pathogenic genes in PE such as HSP90, PAK2, CD247, and others, included in the first 1% of the prioritized list, so it needs to be explored further on the pathogenesis of PE through an experimental approach [50]. Activation of endothelial antibodies is also a marker of cardiovascular system dysfunction and endothelial dysfunction as well as severe pathology, with multiple organ failure manifestations, which is evidence of the relevance of this area of research to a large number of patients [51].…”
Section: Role Of Immunology Cells In Pementioning
confidence: 99%